2017
DOI: 10.1016/j.jad.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptom composites associated with cortisol stress reactivity in adolescents

Abstract: Background Altered hypothalamic-pituitary-adrenal (HPA) function is common in youth with major depressive disorder (MDD) but variability in the strength and direction of HPA alterations has prompted a search for symptom-based subtypes with unique neuroendocrine signatures. This study investigated the extent to which depressive symptom composites were differentially associated with cortisol responses to psychosocial stress. Methods This study examined salivary cortisol responses to the Trier Social Stress Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…ELS-related aberrant cortisol regulation, in turn, has been associated with emotion dysregulation in youth, including elevated negative affect and social withdrawal (e.g., Alink, Cicchetti, Kim, & Rogosch, 2012; Cicchetti, Rogosch, Gunnar, & Toth, 2010). The decreased cortisol pattern linked to ELS parallels findings in adolescents with higher depressive symptoms (e.g., Morris, Kouros, Meilock, & Rao, 2017). Harkness, Stewart, and Wynne-Edwards (2011) reported that a history of maltreatment interacted with subsequent high levels of depressive symptoms to predict decreased cortisol responses to a psychosocial stressor in adolescents.…”
supporting
confidence: 71%
“…ELS-related aberrant cortisol regulation, in turn, has been associated with emotion dysregulation in youth, including elevated negative affect and social withdrawal (e.g., Alink, Cicchetti, Kim, & Rogosch, 2012; Cicchetti, Rogosch, Gunnar, & Toth, 2010). The decreased cortisol pattern linked to ELS parallels findings in adolescents with higher depressive symptoms (e.g., Morris, Kouros, Meilock, & Rao, 2017). Harkness, Stewart, and Wynne-Edwards (2011) reported that a history of maltreatment interacted with subsequent high levels of depressive symptoms to predict decreased cortisol responses to a psychosocial stressor in adolescents.…”
supporting
confidence: 71%
“…In contrast, emotional recovery has been studied as the ability to return to a baseline level of emotionality after arousal, which can be studied as negative affective persistence to events, or as the level of distress after a stressor has ceased. For example, a recent study that differentiated between stress reactivity and stress recovery found that affective symptoms of depression were associated with increased stress reactivity and fast recovery following a social stress task, whereas neurovegetative symptoms of depression were associated with blunted reactivity and slower recovery following the social stress task among adolescents (Morris et al, 2017). In addition, a recent examination found that depressive symptoms were associated with a more sustained emotional activation to stress, but were not associated with a greater intensity of activation (Lopez-Duran et al, 2015).…”
mentioning
confidence: 99%
“…Two studies reported that adolescents with MDD had greater cortisol response to social stress tests compared with HC whilst the other two found no difference between the groups ( Ming et al., 2017 ; Rao et al., 2008 ; Klimes-Dougan et al., 2014 ; Morris, 2014 ). Morris and colleagues used TSST to compare cortisol reactivity between adolescents with low and high risk for MDD and current MDD, and reported higher cortisol reactivity in the low-risk group compared with MDD and high-risk groups ( Morris Chrystyna et al., 2017 ). Furthermore, adolescents with MDD had significantly higher levels of nocturnal UFC compared with HC ( Rao and Poland, 2009 ).…”
Section: Hypothalamic-pituitary-adrenal (Hpa) Axis In Depressionmentioning
confidence: 99%